ECONOMIC SECURITY OF HIGHER EDUCATION: A SYSTEMIC APPROACH - Nikolay Plotnikov (Вестник Северо-Кавказского федерального университета)
Article talks about the issues of systematic approach to ensuring the economic security of higher education. It identifies the main conclusions of the analysis ofpractices and regulations in the area of national security in 5 years. Based on the analysis revealed the structure of the national security management and systematized legal acts. It recognized the need to supplement the information and the legal framework of the message of the President of the Federal Assembly of the Russian Federation. It concluded that higher education is a priority in national security. Introduced a new concept - an educational security, us the level of state system of higher education in the different periods of national security. The implementation ofnational priorities and innovative development of the economy. Studied the specifics of the security social systems and concluded on the need to address it from a position of economic security. The basic features of higher education in the national security system, where an important role is given to the identiication of patterns of development of higher education. The analysis of the operation of these systems with a 3 directions: the internal structure, and hierarchical management approach.